Maren Sebagai Identitas Budaya Lokal Masyarakat Kei Desa Ohoinol Kecamatan Kei Kecil Timur Kabupaten Maluku Tenggara - Far Far, Gazali (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2021)
Marena is the Kei people's local cultural system, manifested in the bonds of solidarity and identity from the local culture of the Ohoinol village community. There is a cooperation between community group members in Ohoinol village. Maren or Gotongroyong, found in the Kei community, especially in Ohoinol village, is a portrait of social solidarity. The problem in this research is whether the local culture of Maren is still enforced in the scope of life of the Kei people, especially in Ohoinol village, and is upheld by the community regarding a sense of solidarity. To answer the existing problems, researchers used qualitative research methods, and to obtain data in the field, researchers used observation and interview methods. From the research results, the researcher found that the form of participation of the Ohoinol village community towards Maren as a local culture was still perfect, and its application was still the same as a form of solidarity for the Kei people, especially in Ohoinol village.